Why Looking Backward Is Necessary to Looking Forward. Issue 1 (7th December 2018) - Armstrong, Nancy
Abstract : By treating the imaginary element that is "sex, " the deployment of sexuality established one of its most essential internal operating principles; the desire for sex—the desire to have it, to have access to it, to liberate it, to articulate it in discourse, to formulate it in truth. It constituted "sex" itself as something desirable. —Michel Foucault, History of Sexuality, Vol. 1 Although my critical focus has shifted in recent years onto other areas—both earlier and later—of novel studies, I find myself returning to the novels of the 1840s, which is, in my view, the pivotal moment in the history and theory of the British novel. This is the moment when novels relegated forever to the past a future that ensured domestic contentment. During the period from 1847 to 1900, as Georg Lukács tells the story, the historical novel faltered and then froze in its tracks, as the narrative of an individual caught in the winds of historical change capitulated to descriptions of demonically fetishized objects that obscured the engines of change. What Lukács doesn't mention is that, halfway through that same period, novels abruptly ceased to formulate a country house providing what Hannah Arendt has called "a model of national housekeeping." From the ashes of that bourgeois appropriation of certain aspects of the genteel way of life, the novels of the 1840s assembled a single-family household as a kinship system uniquely capable of operating at every level of English society. To go by these novels, one would think that belonging to such a household was not only the same as belonging to English society itself but was also necessary to one's biological survival. In returning to that moment, I want to consider, more pointedly, what these two observations concerning the form of the Victorian novel have to do with one another, a question that was very much in the air in 1977, when I received my doctorate and took up my first university post.